Kecerdasan Emosional dan Perilaku Prososial pada Siswa SMP Panca Budi - Michael Wutama; Beby Astri Tarigan; Lavenia Natheni; Rina Mirza; Nur Afni Safarina (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the relationship between Emotional Intelligence and Prosocial Behaviour among students of SMP Panca Budi Medan. A quantitative method was utilized, involving a sample of 191 students selected using Disproportionate Stratified Random Sampling. Data was collected using two main instruments: a 30-item Prosocial Behaviour scale and a 29-item Emotional Intelligence scale. Data analysis was conducted using the Pearson Product-Moment correlation test with the aid of SPSS Statistics 24 for Windows. The results revealed a correlation coefficient (r) of 0.326 with a significant value (p-value) of 0.000 (p < 0.05), indicating that there is a positive and significant relationship between Emotional Intelligence and Prosocial Behaviour. The coefficient of determination (R²) was 0.106, implying that Emotional Intelligence contributes 10.6% to Prosocial Behaviour, whereas the remaining 89.4% was influenced by variables not addressed in this study's parameters. These results underscore the significant contribution of Emotional Intelligence in promoting Prosocial Behavior.